Competitive Advantages and Performance of the Halal Industry in Micro, Small and Medium Enterprises (MSMEs): Systematic Literature Review - Alimatul Farida; Muhamad Ahsan; Burhan Djamaluddin; Mohd. Sollehudin Bin Shuib (CV. Satria Jaya, 2025)
The objective of this study is to classify and identify scientific article publications and conduct a systematic analysis of the current literature to develop a comprehensive understanding and provide deeper knowledge insights regarding the study of competitive advantages and halal industry performance in Micro, Small, and Medium Enterprises (MSMEs). The research methodology employs the Systematic Literature Review approach, utilizing a review process based on the PRISMA protocol. The study selected 17 articles from Scopus, Google Scholar, PubMed, and Semantic Scholar database sources that met the specified criteria. The data were categorized based on the number of article publications, research methods, research subjects, research focus, and research locus. The findings of the literature review study identify factors that influence the competitive advantage of the halal industry in MSMEs, including social capital, innovation, human resource competence, marketing strategies, sharia funding innovations, public-private partnerships, and compliance with halal standardization. Furthermore, the performance of the halal industry in MSMEs can be evaluated through financial statements, marketing performance, working capital or funding, information technology capabilities, organizational learning, and self-efficacy. This study contributes to the existing literature by systematically identifying and analyzing factors that affect the competitive advantage and measurement of halal industry performance in MSMEs.